Composite sound insulation and heat preservation board for high humidity and high salt environment and preparation method thereof

CN122919097APending Publication Date: 2026-10-16IANGSU COLLEGE OF ENG & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611426800.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-15
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0006]针对上述现有技术,本发明要解决的技术问题是:克服现有建筑分户楼板隔声保温板在高湿高盐环境中长期服役时,因氯离子侵蚀导致芯材劣化、分层、粉化、隔声保温性能下降的缺陷

Benefits of technology

[0030] 1. Existing sound insulation and heat insulation boards for individual apartment floors are designed with heat insulation, sound insulation, and ease of construction as their technical objectives, but have not paid attention to the problem of chloride ion corrosion in high humidity and high salt environments. This invention solves the engineering problem of powdering, delamination, and failure of sound insulation and heat insulation boards for individual apartment floors under long-term chloride ion corrosion, and fills the gap in this technical field in terms of salt resistance and durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122919097A_ABST
    Figure CN122919097A_ABST
Patent Text Reader

Abstract

The application discloses a composite sound insulation and heat preservation board for high-humidity and high-salt environment and a preparation method thereof, and belongs to the technical field of building floor heat preservation and sound insulation. The composite sound insulation and heat preservation board comprises a sandwich layer main structure, and the sandwich layer main structure comprises a sound insulation and heat preservation core material and a polymer mortar protective layer. The core material is formed by mixing and pressing components such as modified graphite polyphenyl particles, plasma-coupling agent double-interface modified rubber particles and hydrotalcite chloride ion capturing fillers pretreated by ionic liquids. A nano-aerogel salt-blocking transition film is arranged between the core material and the protective layer. The protective layer is a double-layer functional gradient structure comprising an inner layer hydrophobic transition layer and an outer layer chloride ion blocking layer. An inorganic sealing and salt-blocking frame is integrally formed on four side edges of the sandwich layer main structure, and a six-surface fully-closed salt-blocking protection system is formed. The composite sound insulation and heat preservation board has good high-humidity and high-salt environment durability, and has no pulverization and stratification defects after 300 hours of neutral salt spray test, and the softening coefficient is greater than or equal to 0.88.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of building floor insulation and soundproofing technology, specifically to a composite soundproof and heat-insulating board for high humidity and high salt environments and its preparation method. Background Technology

[0002] With the promotion of green building and healthy housing concepts, the thermal and sound insulation performance of building floor slabs is receiving increasing attention. Floor sound insulation is a crucial factor in ensuring a safe residential environment, while floor thermal insulation is a key aspect of building energy conservation. Currently, sound insulation and thermal insulation panels for building floor slabs have become the mainstream technical solution for addressing heat transfer and noise interference between floors.

[0003] Chinese invention patent application CN104863295A discloses a non-removable composite thermal insulation and sound insulation board for individual apartment floors and its construction method. It includes a bottom polymer lightweight mortar reinforcement layer, a lower polymer mortar bonding layer, an alkali-resistant mesh fabric, a thermal insulation and sound insulation layer, and an upper polymer mortar bonding layer. The thermal insulation and sound insulation layer is a prefabricated board such as XPS extruded polystyrene board, EPS polystyrene board, polyurethane board, or inorganic insulation board. Chinese invention patent CN110424625B discloses a formwork-free composite thermal insulation and sound insulation board and a construction method for thermal insulation and sound insulation floors. Its lightweight thermal insulation and sound insulation layer has polymer cement mortar reinforcement layers on both the upper and lower sides, with glass fiber mesh fabric inside the reinforcement layers. The lightweight thermal insulation and sound insulation layer is made of extruded polystyrene foam board, molded polystyrene foam board, foam glass board, polyurethane foam board, or cement-based polystyrene particle composite insulation board. Chinese invention patent CN117484672B discloses a Class A composite thermal insulation and sound insulation board and its preparation method, which uses a Class B1 polystyrene board combined with inorganic slurry and cement fiberglass mesh. The common feature of the aforementioned prior art is that it uses prefabricated organic foam board as the thermal insulation and sound insulation core material, combined with upper and lower polymer mortar protective layers to form a sandwich structure, addressing the technical problems of "thermal insulation + sound insulation + ease of construction".

[0004] However, none of the aforementioned existing technologies have considered the long-term durability issues under high humidity and high salinity environments. In coastal areas, saline-alkali areas, and environments surrounding chemical industrial parks, the air and interiors of buildings contain large amounts of chloride ions (Cl). - Under the influence of moisture, chloride ions penetrate the interior of the board through capillary adsorption, diffusion, and wet-dry cycles. Studies have shown that in the alternating wet and dry conditions of marine tidal zones, chloride ions penetrate into concrete and composite materials at a relatively rapid rate. Long-term chloride ion erosion leads to the powdering of the polymer mortar protective layer, aging and degradation of the organic insulation core material, and delamination of the interface between the core material and the protective layer, ultimately causing the overall structural failure of the board and a significant decrease in sound insulation and thermal insulation performance.

[0005] Currently, there is no effective systematic solution to the problem of chloride ion corrosion in composite sound insulation and heat insulation boards used in individual apartment floors. Summary of the Invention

[0006] The technical problem to be solved by the present invention in view of the above-mentioned prior art is to overcome the defects of existing building floor sound insulation boards in long-term service in high humidity and high salt environment, such as core material deterioration, delamination, pulverization, and decreased sound insulation and heat insulation performance due to chloride ion corrosion.

[0007] To address the aforementioned problems, this invention provides a composite sound insulation and heat preservation board for high humidity and high salt environments, which is applicable to building floor slabs. It includes a sandwich layered main structure, comprising a sound insulation and heat preservation core material and polymer mortar protective layers disposed on the upper and lower sides of the sound insulation and heat preservation core material.

[0008] The sound insulation and thermal insulation core material is formed by pressing the following components: modified graphite polystyrene particles, inorganic lightweight aggregate, rubber particles with a surface modified by a plasma-coupling agent dual interface, hydrotalcite chloride ion capturing filler pretreated with ionic liquid, inorganic antifungal and antibacterial filler, and inorganic binder. The modified graphite polystyrene particles are graphite polystyrene particles with a silane salt-resistant layer coated on the surface. The anion exchange capacity of the hydrotalcite chloride ion capturing filler pretreated with ionic liquid is ≥12mmol / g.

[0009] A nano-aerogel salt-blocking transition membrane is provided between the sound insulation and heat insulation core material of the sandwich layered main structure and the polymer mortar protective layer. The single layer thickness of the nano-aerogel salt-blocking transition membrane is 0.3-0.5mm, and it is continuously and completely attached to the upper and lower surfaces of the sound insulation and heat insulation core material to block the migration of salt ions to the sound insulation and heat insulation core material.

[0010] The polymer mortar protective layer has a dual-layer functional gradient structure, including an inner hydrophobic transition layer close to the sound insulation and heat insulation core material and an outer chloride ion blocking layer away from the sound insulation and heat insulation core material.

[0011] The sandwich-like layered main structure has an integrally formed inorganic sealing salt barrier frame on all four sides. The inorganic sealing salt barrier frame and the polymer mortar protective layer together constitute a six-sided fully enclosed salt barrier protection system for the composite sound insulation and heat insulation board, forming a salt-resistant protection system that combines active chemical capture and physical full enclosure.

[0012] The composite sound insulation and heat insulation board has no powdering or delamination defects after 300 hours of neutral salt spray, and the softening coefficient is ≥0.88.

[0013] By weight, the raw materials of the sound insulation and thermal insulation core material include: 22-28 parts modified graphite polystyrene particles, 15-25 parts inorganic lightweight aggregate, 15-20 parts rubber particles with surface modified by plasma-coupling agent dual interface, 3-6 parts hydrotalcite chloride ion capturing filler pretreated with ionic liquid, 3-5 parts inorganic anti-mildew and antibacterial filler, 4-7 parts inorganic binder, and water; the liquid-solid ratio of the sound insulation and thermal insulation core material is 0.35-0.45 (the liquid-solid ratio refers to the ratio of water to the total mass of all other raw materials except water); the inorganic anti-mildew and antibacterial filler is titanium dioxide composite zeolite powder.

[0014] Rubber particles with plasma-coupling agent dual interface modification were obtained as follows: 10-200 mesh graded rubber particles were placed in a low-temperature plasma treatment device and treated for 40-80 seconds in an argon atmosphere with a power of 250-350W and a gas flow rate of 0.5-1.0L / min. Subsequently, they were sprayed with a 1.2%-1.8% γ-aminopropyltriethoxysilane ethanol solution and dried at 55-65℃ to constant weight. The time interval between the plasma-treated rubber particles exiting the chamber and being sprayed with the coupling agent solution was ≤30 seconds, and the activity of activated surface free radicals was retained through timely spraying.

[0015] The hydrotalcite chloride ion capturing packing material pretreated with ionic liquid is a Mg / Al type hydrotalcite with a Mg to Al molar ratio of 2:1 to 4:1. The ionic liquid pretreatment involves placing the hydrotalcite in a 0.8–1.2 wt% aqueous solution of 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid, ultrasonically treating it at 50–60 °C for 45–75 minutes, filtering it, washing it with deionized water until the pH of the filtrate is neutral, drying it at 60–70 °C, and grinding it through a 200-mesh sieve to prepare the hydrotalcite chloride ion capturing packing material pretreated with ionic liquid and possessing high chloride ion exchange activity.

[0016] The inner hydrophobic transition layer is a polysiloxane hydrophobic modified mortar layer with a thickness of 0.8–1.2 mm; the outer chloride ion blocking layer has a thickness of 1.8–2.5 mm, and the outer layer is inlaid with alkali-resistant glass fiber mesh.

[0017] The outer chloride ion blocking layer is composed of fluorosilicone modified waterproof and salt-resistant polymer mortar. By weight, its raw materials include: 45 parts ordinary silicate cement, 35 parts quartz sand, 8 parts fluorosilicone emulsion, 5 parts salt-resistant corrosion inhibitor, 2 parts water-reducing agent, 1 part mildew-resistant additive, and water. The liquid-to-solid ratio of the fluorosilicone modified waterproof and salt-resistant polymer mortar is 0.40 to 0.50 (the liquid-to-solid ratio refers to the ratio of water to the total mass of all other raw materials except water). The chloride ion penetration depth of the fluorosilicone modified waterproof and salt-resistant polymer mortar is ≤0.1mm.

[0018] The inorganic sealing salt-barrier frame is 10mm wide and is made of high-alumina cement, ultrafine silica fume, and fluorosilicone emulsion in a mass ratio of 60:20:20. It is extruded and integrally formed with the sandwich-layered main body. The sound insulation and heat insulation core material is 18-25mm thick, with a compressive strength ≥0.45MPa, a drying shrinkage value ≤1.2mm / m, and a combustion performance of A2 grade. The overall thermal conductivity of the composite sound insulation board is ≤0.040W / (m·K). When the composite sound insulation board is used with a 5mm or 7mm thick salt-resistant modified shock-absorbing and damping pad for the floor slab of a separate unit, the weighted standardized impact sound pressure level of the floor slab is ≤60dB, and the airborne sound insulation is ≥52dB.

[0019] The present invention also provides a method for preparing the above-mentioned composite sound insulation and heat insulation board, comprising the following steps:

[0020] S1. Salt-resistant coating and dual modification pretreatment of organic aggregates: Graphite polystyrene particles are placed in a silane salt-resistant coating solution and then dried in a forced-air condition at 55-65℃ to form a complete silane salt-resistant layer on the surface of the graphite polystyrene particles, thus obtaining modified graphite polystyrene particles; rubber particles are treated to obtain rubber particles with surface modified by plasma-coupling agent dual interface.

[0021] S2. Hydrotalcite ionic liquid pretreatment: Mg / Al type hydrotalcite is modified to obtain hydrotalcite chloride ion capturing packing material pretreated with ionic liquid.

[0022] S3. Pressing of sound insulation and heat insulation core material blank: Modified graphite polystyrene particles, rubber particles with surface modified by plasma-coupling agent dual interface, inorganic lightweight aggregate, hydrotalcite chloride ion capturing filler pretreated with ionic liquid, inorganic mildew-proof and antibacterial filler, and inorganic binder are mixed according to the above ratio, water is added and the liquid-solid ratio is controlled at 0.35-0.45, and after stirring evenly, it is sent into the mold for pressing to obtain the core material blank;

[0023] S4. Nano-aerogel salt barrier transition film bonding: Aerogel film-forming liquid is rolled onto the upper and lower surfaces of the core material blank and dried with hot air to form a continuous and undamaged nano-aerogel salt barrier transition film.

[0024] S5. Double-sided synchronous hot-pressed composite double-layer functional gradient protective layer: The inner hydrophobic transition layer and the outer chloride ion blocking layer are sequentially composited on the outside of the salt barrier transition membrane, so that the interface of the protective layer, the salt barrier transition membrane and the sound insulation and heat insulation core material are fused together.

[0025] S6. Synchronous extrusion of inorganic sealing salt barrier frame on the side: Inorganic sealing salt barrier frame is extruded synchronously along the four sides of the board, and the frame and the main body of the board are formed in one piece without splicing gaps.

[0026] S7. Three-stage gradient humid heat curing: The formed boards are cured in three progressive stages.

[0027] S8. Cutting and Sealing of Finished Products: After curing, cut the product into standard-sized boards, apply sealant to the cut surfaces, and seal all six sides of the board to obtain a composite sound insulation and heat insulation board for high humidity and high salt environments.

[0028] In step S3, the pressing process involves first applying a low-pressure pre-compression of 0.06–0.09 MPa for 8–15 seconds, followed by a high-pressure final compression of 0.9–1.1 MPa for 35–55 seconds, with the compression ratio controlled at 1.6–1.8. In step S5, the process conditions for double-sided synchronous hot pressing are: temperature 80℃, pressure 0.6 MPa, and holding pressure for 8 minutes. In step S7, the three-stage progressive curing process is as follows: the first stage is low-temperature curing at 30℃ and 90% humidity for 12 hours; the second stage is medium-temperature curing at 55℃ and 70% humidity for 24 hours; and the third stage is high-temperature weathering curing at 70℃ and 50% humidity for 18 hours.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] 1. Existing sound insulation and heat insulation boards for individual apartment floors are designed with heat insulation, sound insulation, and ease of construction as their technical objectives, but have not paid attention to the problem of chloride ion corrosion in high humidity and high salt environments. This invention solves the engineering problem of powdering, delamination, and failure of sound insulation and heat insulation boards for individual apartment floors under long-term chloride ion corrosion, and fills the gap in this technical field in terms of salt resistance and durability.

[0031] 2. This invention constructs a three-dimensional synergistic salt-blocking system of "active chemical capture + physical gradient barrier + six-sided full enclosure", forming a layered progressive protection chain from chemical to physical, from the inside to the outside, and from the large surface to the sides:

[0032] Active chemical capture inside the core material: Rubber particles modified by plasma-coupling agent dual interface are used to eliminate chloride ion infiltration into the micro-channels of the organic-inorganic interface inside the core material; at the same time, hydrotalcite chloride ion capturing filler (anion exchange capacity ≥12mmol / g) pretreated with ionic liquid actively chemically captures chloride ions that have infiltrated into the core material, forming a dual guarantee of "source blocking + active removal" at the core material level.

[0033] Interfacial physical barrier: The nano-aerogel salt barrier transition membrane (0.3-0.5mm continuous and complete) forms a physical barrier layer between the core material and the protective layer, blocking chloride ions from migrating into the core material along the interfacial capillary channels.

[0034] External gradient protection: The dual-layer functional gradient protection layer (inner layer of polysiloxane hydrophobic transition and outer layer of fluorosilicone modified chloride ion blocking) forms a gradient layer-by-layer salt barrier from hydrophobic to salt resistant, with the outer layer chloride ion penetration depth ≤0.1mm.

[0035] Laterally fully enclosed: The four sides are integrally formed inorganic sealing salt barrier frame and upper and lower protective layers together form a six-sided fully enclosed salt barrier protection system, which prevents chloride ions from entering from the side, a path that is completely ignored by existing technologies.

[0036] 3. Conventional durability designs often come at the cost of sacrificing thermal insulation or sound insulation performance. However, this invention achieves long-term durability in high humidity and high salt environments while maintaining excellent thermal insulation and sound insulation performance, thus achieving a balance of high durability, high thermal insulation, high sound insulation, and high strength. Attached Figure Description

[0037] Figure 1 This is a schematic cross-sectional view of the composite sound insulation and heat preservation board for high humidity and high salt environments in this invention.

[0038] Figure 2 This is a process flow diagram of the preparation method of the composite sound insulation and heat preservation board for high humidity and high salt environment in this invention.

[0039] Explanation of the labels in the diagram:

[0040] 001. Sound insulation and heat insulation core material; 002. Polymer mortar protective layer; 003. Nano aerogel salt barrier transition membrane; 004. Inorganic sealing salt barrier frame; 201. Inner hydrophobic transition layer; 202. Outer chloride ion blocking layer; 203. Alkali-resistant glass fiber mesh. Detailed Implementation

[0041] Example 1

[0042] Please see Figure 1-2 This embodiment provides a composite sound insulation and heat preservation board for high humidity and high salt environment, and its preparation method includes the following steps.

[0043] (a) Graphite polystyrene particles coated with silane for salt resistance

[0044] Take graphite polystyrene particles (particle size 1-3 mm, bulk density 18-25 kg / m³) 3 25 parts by weight were placed in a 2.0 wt% vinyltrimethoxysilane ethanol solution and soaked in a sealed container for 15 minutes. After removal, the particles were dried in a forced-air dryer at 60°C for 2 hours to form a complete silane salt-resistant layer on the surface of the graphite polystyrene particles, thus obtaining modified graphite polystyrene particles for later use.

[0045] (II) Plasma-coupling agent dual-interface modification of rubber particles

[0046] Take 17 parts by weight of waste rubber granules with a particle size distribution of 10-200 mesh (10 mesh: 50 mesh: 200 mesh = 1:2:1), place them in a low-temperature plasma treatment device, introduce argon gas at a flow rate of 0.8 L / min, and treat for 60 seconds at a power of 300 W. After treatment, quickly remove them from the chamber and spray them with a 1.5 wt% γ-aminopropyltriethoxysilane ethanol solution within 20 seconds (the spray volume should be sufficient to uniformly wet the particle surface). Then, dry them at 60℃ with forced air until constant weight to obtain rubber granules with a surface modified by a plasma-coupling agent dual interface, for later use.

[0047] The surface free radicals of the plasma-activated rubber particles exhibit rapid decay characteristics. Prolonged exposure to air can lead to activation failure and a significant decrease in interfacial bonding. In this embodiment, the interval between exiting the chamber and spraying is controlled to be 20 seconds (≤30 seconds) to maximize the retention of highly active surface free radicals, achieve covalent bonding between the coupling agent and the rubber surface, and significantly improve the compatibility of the organic-inorganic interface.

[0048] (III) Pretreatment of hydrotalcite ionic liquid

[0049] Four parts by weight of Mg / Al type hydrotalcite (Mg to Al molar ratio of 3:1) were placed in a 1.0 wt% aqueous solution of 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid and sonicated at 55°C for 60 minutes (ultrasonic power 300W, frequency 40kHz). After filtration, the solution was washed with deionized water until the pH of the filtrate was neutral, dried at 65°C, and then ground through a 200-mesh sieve to obtain hydrotalcite chloride ion capturing packing material with high chloride ion exchange activity after ionic liquid pretreatment, which was then used for later use. The anion exchange capacity of the same hydrotalcite raw material without ionic liquid pretreatment was 7.2 mmol / g, while after pretreatment in this example, its anion exchange capacity increased to 13.5 mmol / g (anion exchange capacity test method: silver nitrate potentiometric titration method, using sodium chloride standard solution as titrant, to determine the amount of chloride ion exchange adsorption of the hydrotalcite sample; for specific operation, refer to the relevant method in JC / T2357-2016).

[0050] (iv) Raw material preparation

[0051] Take 4 parts by weight of titanium dioxide composite zeolite powder (particle size ≤200 mesh, titanium dioxide loading 5-10 wt%) for later use. Use 20 parts by weight of vitrified microspheres (particle size 0.5-1.5 mm) as the inorganic lightweight aggregate. Use 5 parts by weight of ordinary Portland cement (P·O 42.5 grade) as the inorganic binder.

[0052] This embodiment uses titanium dioxide composite zeolite powder as an inorganic antifungal and antibacterial filler for illustrative purposes. The present invention is not limited to this single filler. Those skilled in the art can select other inorganic fillers with antifungal and antibacterial properties (such as silver-loaded zeolite, zinc oxide / zeolite composite powder, etc.) to achieve similar effects according to actual needs.

[0053] (v) Pressing of sound insulation and heat insulation core material blanks

[0054] 25 parts by weight of the modified graphite polystyrene particles, 17 parts by weight of rubber particles with a surface modified by a plasma-coupling agent dual interface, 20 parts by weight of vitrified microspheres, 4 parts by weight of hydrotalcite chloride ion capturing filler pretreated with ionic liquid, 4 parts by weight of titanium dioxide composite zeolite powder, and 5 parts by weight of ordinary silicate cement were added to a forced mixer and dry-mixed for 5 minutes to ensure uniform mixing of all components. Then, water was added, controlling the liquid-to-solid ratio at 0.45 (i.e., the ratio of water to the total mass of all other raw materials excluding water is 0.45), and wet-mixed for 3 minutes to obtain a uniform mixture.

[0055] The mixture is fed into a molding die and subjected to a gradient compression molding process: first, a low-pressure pre-compression of 0.07 MPa for 12 seconds is applied to initially shape the material, followed by a high-pressure final compression of 1.0 MPa for 45 seconds, with the compression ratio controlled at 1.7. After demolding, a sound insulation and heat preservation core material blank with a thickness of 22 mm is obtained.

[0056] (vi) Nano-aerogel salt barrier transition membrane bonding

[0057] The upper and lower surfaces of the core material blank obtained in step (V) are uniformly coated with a nano-silica aerogel film-forming liquid using a roller coating method. The aerogel film-forming liquid is prepared as follows: nano-silica aerogel powder (particle size 10-30 nm) is dispersed in anhydrous ethanol, the solid content of the aerogel powder is controlled at 5-8 wt%, and 1%-5% of silane coupling agent (KH-550) is added as a dispersing aid. The mixture is ultrasonically dispersed for 30 minutes to obtain the final product (those skilled in the art can also use commercially available silica aerogel dispersion with a solid content of 5-8 wt% and a viscosity of 50-100 mPa·s). The coating amount is based on forming a wet film thickness of 0.5-0.7 mm. Subsequently, the film is dried with hot air at 50°C to form a single-layer, continuous, intact, and undamaged nano-aerogel salt barrier transition film 003 with a thickness of 0.4 mm on the upper and lower surfaces of the core material blank.

[0058] (vii) Double-sided synchronous hot-pressed composite double-layer functional gradient protective layer

[0059] Prepare the inner hydrophobic transition layer mortar: by weight, take 100 parts of ordinary silicate cement (P·O 42.5 grade), 150 parts of quartz sand (40-70 mesh), 5 parts of polysiloxane powder hydrophobic agent, 3 parts of redispersible latex powder, and 0.2 parts of cellulose ether, add water and control the liquid-solid ratio to 0.45, and stir to mix evenly.

[0060] Preparation of the outer chloride ion blocking layer mortar: By weight, take 45 parts of ordinary silicate cement (P·O 42.5 grade), 35 parts of quartz sand (40-70 mesh), 8 parts of fluorosilicone emulsion, 5 parts of calcium nitrite (as a salt-resistant corrosion inhibitor filler), 2 parts of polycarboxylate-based water-reducing agent, and 1 part of thiazole-based antifungal agent. Add water and control the liquid-solid ratio at 0.45. Stir and mix evenly to obtain fluorosilicone-modified waterproof and salt-resistant polymer mortar. The mortar was tested for chloride ion penetration depth (referring to the test procedure of RCM method in GB / T 50082-2024, preparing standard specimens of the core material layer, and using the large surface of the board as the chloride ion solution exposure surface for measurement to characterize the chloride ion penetration resistance of the core material layer). The chloride ion penetration depth was ≤0.1mm.

[0061] Using a double-roller hot press, at a temperature of 80℃ and a pressure of 0.6MPa, the inner hydrophobic transition layer 201 mortar (1.0mm thick) is first rolled onto the outer side of the nano-aerogel salt-barrier transition membrane 003 on the upper and lower surfaces of the sound insulation and heat-insulating core material blank, followed by the outer chloride ion blocking layer 202 mortar (2.0mm thick). An alkali-resistant glass fiber mesh 203 (mesh size 5mm×5mm, unit area mass ≥160g / m²; the mesh specifications used in this embodiment are only examples, and those skilled in the art can select other specifications of alkali-resistant glass fiber mesh to achieve similar effects according to actual needs) is embedded in the outer chloride ion blocking layer 202. The alkali-resistant glass fiber mesh 203 is located in the middle of the thickness direction of the outer chloride ion blocking layer 202 (approximately 1.0mm deep from the outer surface). The pressure is maintained for 8 minutes, causing the interfaces of the polymer mortar protective layer 002, the nano-aerogel salt-barrier transition membrane 003, and the sound insulation and heat-insulating core material 001 to fuse together.

[0062] (viii) Synchronous extrusion of side inorganic seal salt barrier frame

[0063] Along the four sides of the sheet material obtained in step (vii), an inorganic sealing salt barrier frame 004 is simultaneously extruded using an extrusion molding machine. The frame material is a compound of high-alumina cement, ultrafine silica fume, and fluorosilicone emulsion in a mass ratio of 60:20:20. The inorganic sealing salt barrier frame 004 is 10mm wide and is formed in one piece with the sandwich-layered main body without any splicing gaps.

[0064] (ix) Three-stage gradient moist heat curing

[0065] The molded sheet obtained in step (eight) is sent to the curing room and undergoes three progressive curing stages:

[0066] Phase 1: Temperature 30℃, ambient humidity 90%, low-temperature moisturizing maintenance for 12 hours;

[0067] Second stage: Temperature 55℃, ambient humidity 70%, medium-temperature curing for 24 hours;

[0068] Phase 3: Temperature 70℃, ambient humidity 50%, high-temperature weathering curing for 18 hours.

[0069] The curing room has a heating rate of 10℃ / hour and an air velocity of 0.3m / s.

[0070] (x) Cutting and sealing of finished products

[0071] After curing, the board is cut to standard size (1200mm×600mm), and a sealant with the same composition as the inorganic salt barrier 004 is applied to the cut surfaces to complete the six-sided sealing of the board. After performance sampling and testing, it is put into storage.

[0072] The composite sound insulation and heat insulation board prepared in this embodiment has a total thickness of 28mm (22mm for the sound insulation and heat insulation core material 001 + 1.0mm for each inner hydrophobic transition layer 201 + 2.0mm for each outer chloride ion blocking layer 202). Its structural features are as follows: the top and bottom surfaces are covered by a polymer mortar protective layer 002 (i.e., the inner hydrophobic transition layer 201 + the outer chloride ion blocking layer 202); the four sides are covered by an integrally formed inorganic sealing salt-barrier frame 004; and the sealant applied to the cut surfaces after cutting provides secondary sealing for any minor defects that may exist in the frame. These three components work together to construct a complete six-sided fully enclosed salt-barrier protection system. The performance indicators are shown in Table 1.

[0073] Table 1 Performance test results of the product in Example 1

[0074] Note: Impact sound pressure level and airborne sound insulation were tested when a 7mm thick salt-resistant modified damping pad was used for the floor slab of each unit.

[0075] The chloride ion penetration depth of the outer chloride ion blocking layer 202 mortar, tested alone, is ≤0.1mm; the chloride ion penetration depth of the core material layer of the finished board is 2.8mm. These two tests correspond to different test objects (single-layer mortar material vs. core material), and do not constitute a contradiction.

[0076] Example 2

[0077] The only difference between this embodiment and Embodiment 1 is that the raw materials for each component are taken at the lower value of a wider range.

[0078] Specifically, the composition includes 22 parts by weight of modified graphite polystyrene particles, 15 parts by weight of inorganic lightweight aggregate (vitrified microspheres), 15 parts by weight of rubber particles with a surface modified by a plasma-coupling agent dual interface, 3 parts by weight of hydrotalcite chloride ion capturing filler pretreated with ionic liquid, 3 parts by weight of titanium dioxide composite zeolite powder, and 4 parts by weight of ordinary silicate cement. The plasma treatment conditions are: power 250W, treatment time 40 seconds; the ionic liquid pretreatment conditions are: ionic liquid concentration 0.8wt%, ultrasonic temperature 50℃, ultrasonic time 45 minutes.

[0079] The composite sound insulation and heat insulation board prepared in this embodiment was tested and found to have no powdering or delamination defects after 300 hours of neutral salt spray, a softening coefficient of 0.88 (meeting the requirement of ≥0.88 specified in this invention), a thermal conductivity of 0.040 W / (m·K), and a compressive strength of 0.45 MPa. All performance indicators meet the aforementioned performance requirements of the product.

[0080] Example 3

[0081] The only difference between this embodiment and Embodiment 1 is that the raw materials for each component are selected from the higher values ​​of a wider range.

[0082] Specifically, the composition includes 28 parts by weight of modified graphite polystyrene particles, 25 parts by weight of inorganic lightweight aggregate (expanded perlite), 20 parts by weight of rubber particles with a surface modified by a plasma-coupling agent dual interface, 6 parts by weight of hydrotalcite chloride ion capturing filler pretreated with ionic liquid, 5 parts by weight of titanium dioxide composite zeolite powder, and 7 parts by weight of ordinary silicate cement. The plasma treatment conditions are: power 350W, treatment time 80 seconds; the ionic liquid pretreatment conditions are: ionic liquid concentration 1.2wt%, ultrasonic temperature 60℃, ultrasonic time 75 minutes.

[0083] The composite sound insulation and heat insulation board prepared in this embodiment was tested and found to have no powdering or delamination defects after 300 hours of neutral salt spray. It has a softening coefficient of 0.93, a thermal conductivity of 0.036 W / (m·K), and a compressive strength of 0.48 MPa. All performance indicators are better than the aforementioned performance limits of the product.

[0084] Comparative Example 1

[0085] The only difference between this comparative example and Example 1 is that the nano-aerogel salt-barrier transition membrane 003 bonding step is omitted. That is, the nano-aerogel salt-barrier transition membrane 003 is not placed on the surface of the sound insulation and heat-insulating core material blank. Instead, a polymer mortar protective layer 002 (i.e., inner hydrophobic transition layer 201 + outer chloride ion blocking layer 202) is directly composited on the surface of the core material blank. The remaining raw material ratios and preparation processes are the same as in Example 1.

[0086] The board prepared in this comparative example was tested and found to show obvious pulverization after 300 hours of neutral salt spray resistance, with a softening coefficient of 0.62 and a chloride ion penetration depth of 9.3 mm (significantly increased). Other performance indicators showed varying degrees of decline compared to Example 1.

[0087] Comparative Example 2

[0088] The only difference between this comparative example and Example 1 is that the synchronous extrusion step of the side inorganic sealing salt barrier frame 004 is omitted, that is, the inorganic sealing salt barrier frame 004 is not set on the four sides of the plate. The other raw material ratios and preparation processes are the same as in Example 1.

[0089] The board prepared in this comparative example was tested and found that after 300 hours of neutral salt spray resistance, severe salt crystallization and corrosion appeared on the sides. Chloride ions penetrated from the sides to the interior to a depth of 7.8 mm, the softening coefficient was 0.58, and the overall structure of the board showed signs of delamination.

[0090] Comparative Example 3

[0091] The only difference between this comparative example and Example 1 is that the hydrotalcite was not pretreated with ionic liquid; untreated Mg / Al type hydrotalcite raw material (anion exchange capacity 7.2 mmol / g) was used directly. All other raw material ratios and preparation processes were the same as in Example 1.

[0092] The board prepared in this comparative example was tested and found that the anion exchange capacity of the hydrotalcite filler inside the core material was only 7.2 mmol / g, and moderate pulverization occurred after 300 hours of neutral salt spray resistance. The softening coefficient was 0.71, and the chloride ion penetration depth was 6.2 mm.

[0093] Comparative Example 4

[0094] The only difference between this comparative example and Example 1 is that the rubber particles are not subjected to plasma treatment, but only to silane coupling agent impregnation modification (i.e., single silane modification). The remaining raw material ratios and preparation processes are the same as in Example 1.

[0095] The board prepared in this comparative example was tested and found that the interfacial bond strength between the rubber particles and the inorganic cementitious material was significantly lower than that in Example 1 (0.18 MPa in Example 1 and 0.09 MPa in this comparative example; the interfacial bond strength test method was: referring to the tensile bond strength test method in JGJ 144-2019, the bond strength between the rubber particles and the cement mortar matrix was tested). After 300 hours of neutral salt spray, interfacial delamination occurred, the softening coefficient was 0.69, and the compressive strength was 0.35 MPa.

[0096] Comparative Example 5

[0097] The only difference between this comparative example and Example 1 is that the polymer mortar protective layer 002 does not adopt a double-layer functional gradient structure, but instead adopts a single-layer homogeneous fluorosilicone modified waterproof and salt-resistant polymer mortar layer (thickness 3.0 mm). The remaining raw material ratios and preparation processes are the same as in Example 1.

[0098] The board prepared in this comparative example was tested and found that after 300 hours of neutral salt spray resistance, microcracks appeared on the outer layer, the softening coefficient was 0.65, and the chloride ion penetration depth was 8.1 mm.

[0099] Comparative Example 6

[0100] This comparative example was prepared according to the typical sandwich structure sound insulation and heat insulation board scheme for apartment floors in the prior art: XPS extruded board (22mm thick) was used as the heat insulation and sound insulation layer, and polymer mortar protective layers (2mm thick on each side, with built-in alkali-resistant glass fiber mesh) were set on the top and bottom. The curing conditions were conventional standard curing (temperature 20±2℃, relative humidity ≥95%, curing for 28 days), and it does not involve any salt barrier design of the present invention.

[0101] The board prepared in this comparative example was tested and found to be completely pulverized and ineffective after 300 hours of neutral salt spray resistance, with a softening coefficient of 0.45 and a chloride ion penetration depth exceeding 15 mm. All performance indicators were far lower than those of Example 1.

[0102] Summary of performance test results

[0103] The durability-related performance test results of Examples 1-3 and Comparative Examples 1-6 are summarized in Table 2, and the physical, mechanical and sound insulation performance test results are summarized in Table 3.

[0104] Table 2. Durability test results of Examples 1-3 and Comparative Examples 1-6

[0105] Table 3. Test results of physical, mechanical and sound insulation performance of Examples 1-3 and Comparative Examples 1-6

[0106] Note: Impact sound pressure level and airborne sound insulation were tested when a 7mm thick salt-resistant modified damping pad was used for the floor slab of each unit.

[0107] Results Analysis

[0108] The test results in Tables 2 and 3 show that:

[0109] (a) The effectiveness of each layer of protective measures

[0110] Comparative Example 1 (without nano-aerogel salt barrier transition membrane 003) compared to Example 1, Cl- The penetration depth increased from 2.8 mm to 9.3 mm (an increase of 232%), and the softening coefficient decreased from 0.91 to 0.62, indicating that the nano-aerogel salt-barrier transition membrane 003 played an important role in physically blocking chloride ion migration.

[0111] Comparative Example 2 (without side inorganic seal salt barrier frame 004) compared to Example 1, Cl - The penetration depth from the side reached 7.8 mm, and the softening coefficient dropped to 0.58, indicating that the side is a crucial channel for chloride ion intrusion. If the side is not sealed, even with the most robust protection on the top and bottom surfaces, the overall salt-blocking effect of the board will be significantly reduced. Furthermore, the drying shrinkage value of Comparative Example 2 increased from 0.9 mm / m to 1.8 mm / m, demonstrating that the absence of the inorganic sealing salt-blocking frame 004 not only directly led to lateral chloride ion intrusion but also indirectly exacerbated drying shrinkage due to decreased structural density. This highlights the synergistic effect of the frame as a structural reinforcement component, whose contribution extends beyond simple physical salt blocking.

[0112] Comparative Example 3 (hydrotalcite without ionic liquid pretreatment) showed a decrease in anion exchange capacity from 13.5 mmol / g to 7.2 mmol / g compared to Example 1, with Cl... - The penetration depth increased from 2.8 mm to 6.2 mm, indicating that the ionic liquid pretreatment significantly improved the chloride ion capture capacity of the hydrotalcite, which is the key to achieving the "active chemical capture" function.

[0113] Compared to Example 1, Comparative Example 4 (rubber particles modified with only a single silane, without plasma treatment) showed a decrease in interfacial bond strength from 0.18 MPa to 0.09 MPa and a decrease in compressive strength from 0.52 MPa to 0.35 MPa, with interfacial delamination observed after salt spray treatment. This is because plasma treatment generates microscopic roughness and active free radicals on the rubber surface, providing more chemical bonding sites for the silane coupling agent. This results in a strong covalent bond between the coupling agent and the rubber surface, rather than a simple physical coating. This dual modification of "physical activation + chemical grafting" significantly enhances the density of the organic-inorganic interface, microscopically blocking the channels for chloride ions to penetrate along the interface.

[0114] Comparative Example 5 (polymer mortar protective layer 002 is a single layer of homogeneous mortar, without double-layer gradient) compared to Example 1, Cl - The penetration depth increased from 2.8 mm to 8.1 mm, and the softening coefficient decreased from 0.91 to 0.65, indicating that the gradient layer-by-layer salt barrier effect of the double-layer functional gradient protective layer (inner hydrophobic transition layer 201 + outer chloride ion blocking layer 202) is significantly better than that of the single-layer homogeneous protective layer.

[0115] (II) Combination Effect

[0116] Comparative Example 6 (prepared according to a typical sandwich structure scheme in the prior art) Cl - With a penetration depth exceeding 15mm, the softening coefficient was only 0.45, and it completely powdered and failed after 300 hours of salt spray. Comparative examples 1-5, lacking any of the protective features, had a higher Cl... - The penetration depth still reaches 5.8–9.3 mm, and the softening coefficient is only 0.58–0.71, both of which cannot reach the level of the complete solution of this invention (Cl). - The penetration depth is ≤3mm, and the softening coefficient is ≥0.88. Among them, the chloride ion penetration depth of Comparative Example 4 (single modification only) and Comparative Example 5 (single-layer protection) increased by 107% and 189%, respectively. When both key protective features are missing at the same time (Comparative Example 6), the chloride ion penetration depth deteriorates to >15mm. The degree of performance degradation is higher than the simple linear sum of the degradation effects caused by the two defects alone. This shows that the overall protective effect of the combination of multiple protective features of the present invention is better than the simple sum of the effects of each protective feature alone.

[0117] The above description is merely a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Various changes made within the scope of knowledge possessed by those skilled in the art without departing from the concept of the present invention still fall within the scope of protection of the present invention.

Claims

1. A composite sound insulation and heat insulation board for use in high humidity and high salinity environments, characterized in that, It includes a sandwich-like layered main structure, which includes a sound insulation and heat insulation core material (001) and a polymer mortar protective layer (002) disposed on the upper and lower sides of the sound insulation and heat insulation core material (001). The sound insulation and heat insulation core material (001) is formed by pressing the following components: modified graphite polystyrene particles, inorganic lightweight aggregate, rubber particles with surface modified by plasma-coupling agent dual interface, hydrotalcite chloride ion capturing filler pretreated with ionic liquid, inorganic anti-mildew and antibacterial filler, and inorganic binder; the modified graphite polystyrene particles are graphite polystyrene particles with a silane salt-resistant layer on the surface, and the anion exchange capacity of the hydrotalcite chloride ion capturing filler pretreated with ionic liquid is ≥12mmol / g; A nano-aerogel salt-blocking transition membrane (003) is provided between the sound insulation and heat insulation core material (001) of the sandwich layered main structure and the polymer mortar protective layer (002). The single layer thickness of the nano-aerogel salt-blocking transition membrane (003) is 0.3-0.5 mm, and it is continuously and completely attached to the upper and lower surfaces of the sound insulation and heat insulation core material (001) to block the migration of salt ions to the sound insulation and heat insulation core material (001). The polymer mortar protective layer (002) is a double-layer functional gradient structure, including an inner hydrophobic transition layer (201) close to the sound insulation and heat insulation core material (001) and an outer chloride ion blocking layer (202) away from the sound insulation and heat insulation core material (001). The sandwich-like layered main structure has an inorganic sealing salt barrier frame (004) integrally formed on all four sides. The inorganic sealing salt barrier frame (004) and the polymer mortar protective layer (002) together constitute the six-sided fully enclosed salt barrier protection system of the composite sound insulation and heat insulation board, forming a salt-resistant protection system that combines active chemical capture and physical full enclosure.

2. The composite sound insulation and heat insulation board for high humidity and high salinity environments according to claim 1, characterized in that, By weight, the raw materials of the sound insulation and heat insulation core material (001) include: 22-28 parts of modified graphite polystyrene particles, 15-25 parts of inorganic lightweight aggregate, 15-20 parts of rubber particles with surface modified by plasma-coupling agent dual interface, 3-6 parts of hydrotalcite chloride ion capturing filler pretreated with ionic liquid, 3-5 parts of inorganic anti-mildew and antibacterial filler, 4-7 parts of inorganic binder, and water; the liquid-solid ratio of the sound insulation and heat insulation core material is 0.35-0.45; the inorganic anti-mildew and antibacterial filler is titanium dioxide composite zeolite powder.

3. The composite sound insulation and heat insulation board for high humidity and high salinity environments according to claim 1, characterized in that, The surface-modified rubber particles with plasma-coupling agent dual interface are obtained by the following method: rubber particles of 10-200 mesh size are placed in a low-temperature plasma treatment device and treated for 40-80 seconds in an argon atmosphere with a power of 250-350W and a gas flow rate of 0.5-1.0L / min. Then, they are sprayed with a 1.2%-1.8% γ-aminopropyltriethoxysilane ethanol solution and dried at 55-65°C to constant weight. The time interval between the plasma-treated rubber particles exiting the chamber and being sprayed with the coupling agent solution is ≤30 seconds, and the activity of the activated surface free radicals is retained by timely spraying.

4. The composite sound insulation and heat insulation board for high humidity and high salinity environments according to claim 1, characterized in that, The hydrotalcite chloride ion capturing packing material pretreated with ionic liquid is a Mg / Al type hydrotalcite with a Mg to Al molar ratio of 2:1 to 4:

1. The ionic liquid pretreatment involves placing the hydrotalcite in a 0.8–1.2 wt% aqueous solution of 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid, ultrasonically treating it at 50–60°C for 45–75 minutes, filtering it, washing it with deionized water until the pH of the filtrate is neutral, drying it at 60–70°C, and then grinding it through a 200-mesh sieve to prepare the hydrotalcite chloride ion capturing packing material pretreated with ionic liquid and possessing high chloride ion exchange activity.

5. The composite sound insulation and heat insulation board for high humidity and high salinity environments according to claim 1, characterized in that, The inner hydrophobic transition layer (201) is a polysiloxane hydrophobic modified mortar layer with a thickness of 0.8 to 1.2 mm; the outer chloride ion blocking layer (202) has a thickness of 1.8 to 2.5 mm, and the outer chloride ion blocking layer (202) has an alkali-resistant glass fiber mesh (203) built in it.

6. The composite sound insulation and heat insulation board for high humidity and high salinity environments according to claim 5, characterized in that, The outer chloride ion blocking layer (202) is composed of fluorosilicone modified waterproof and salt-resistant polymer mortar. By weight, its raw materials include: 45 parts ordinary silicate cement, 35 parts quartz sand, 8 parts fluorosilicone emulsion, 5 parts salt-resistant corrosion inhibitor filler, 2 parts water-reducing agent, 1 part mildew-resistant additive, and water; the liquid-solid ratio of the fluorosilicone modified waterproof and salt-resistant polymer mortar is 0.40 to 0.50; the chloride ion penetration depth of the fluorosilicone modified waterproof and salt-resistant polymer mortar is ≤0.1 mm.

7. The composite sound insulation and heat insulation board for high humidity and high salinity environments according to claim 1, characterized in that, The inorganic sealing salt-blocking frame (004) is 10mm wide and is made of high-alumina cement, ultrafine silica fume and fluorosilicone emulsion in a mass ratio of 60:20:20, and is extruded and integrally formed with the sandwich layered body. The sound insulation and heat insulation core material (001) is 18-25mm thick, with a compressive strength ≥0.45MPa, a drying shrinkage value ≤1.2mm / m, and a combustion performance of A2 grade. The overall thermal conductivity of the composite sound insulation and heat insulation board is ≤0.040W / (m·K). When the composite sound insulation and heat insulation board is matched with a salt-resistant modified shock-absorbing and damping pad with a thickness of 5mm or 7mm for use in the floor slab of the unit, the weighted standardized impact sound pressure level of the floor slab is ≤60dB and the airborne sound insulation is ≥52dB.

8. A method for preparing a composite sound insulation and heat insulation board for high humidity and high salinity environments as described in any one of claims 1 to 7, characterized in that, Includes the following steps: S1. Salt-resistant coating and dual modification pretreatment of organic aggregates: Graphite polystyrene particles are placed in a silane salt-resistant coating solution and then dried in a forced-air condition at 55-65℃ to form a complete silane salt-resistant layer on the surface of the graphite polystyrene particles, thus obtaining modified graphite polystyrene particles; rubber particles are treated to obtain rubber particles with surface modified by plasma-coupling agent dual interface. S2. Hydrotalcite ionic liquid pretreatment: Mg / Al type hydrotalcite is modified to obtain hydrotalcite chloride ion capturing packing material pretreated with ionic liquid. S3. Pressing of sound insulation and heat insulation core material blank: Modified graphite polystyrene particles, rubber particles with surface modified by plasma-coupling agent dual interface, inorganic lightweight aggregate, hydrotalcite chloride ion capturing filler pretreated with ionic liquid, inorganic mildew-proof and antibacterial filler, and inorganic binder are mixed according to the formula, water is added and the liquid-solid ratio is controlled at 0.35-0.45, and after stirring evenly, it is sent into the mold for pressing to obtain the core material blank; S4. Nano-aerogel salt barrier transition film bonding: Aerogel film-forming liquid is rolled onto the upper and lower surfaces of the core material blank and dried with hot air to form a continuous and undamaged nano-aerogel salt barrier transition film. S5. Double-sided synchronous hot-pressed composite double-layer functional gradient protective layer: The inner hydrophobic transition layer (201) and the outer chloride ion blocking layer (202) are sequentially composited on the outside of the salt barrier transition membrane, so that the polymer mortar protective layer (002), the nano aerogel salt barrier transition membrane (003), and the sound insulation and heat insulation core material (001) are fused together into one. S6. Simultaneous extrusion of side inorganic sealing salt barrier frame (004): Simultaneous extrusion of inorganic sealing salt barrier frame (004) along the four sides of the plate, the frame and the main body of the plate are formed in one piece without splicing gap; S7. Three-stage gradient humid heat curing: The formed boards are cured in three progressive stages. S8. Cutting and Sealing of Finished Products: After curing, cut the product into standard-sized boards, apply sealant to the cut surfaces, and seal all six sides of the board to obtain a composite sound insulation and heat insulation board for high humidity and high salt environments.

9. The method for preparing the composite sound insulation and heat insulation board for high humidity and high salinity environments according to claim 8, characterized in that, The compression molding described in step S3 involves first pre-compressing with a pressure of 0.06 to 0.09 MPa for 8 to 15 seconds, and then pressing with a pressure of 0.9 to 1.1 MPa for 35 to 55 seconds, with the compression ratio controlled at 1.6 to 1.

8.

10. The method for preparing the composite sound insulation and heat insulation board for high humidity and high salinity environments according to claim 8, characterized in that, The process conditions for double-sided synchronous hot pressing in step S5 are: temperature 80℃, pressure 0.6MPa, and holding pressure for 8min; the three-stage progressive curing in step S7 are: first stage low temperature curing at 30℃ and 90% humidity for 12h, second stage medium temperature curing at 55℃ and 70% humidity for 24h, and third stage high temperature weathering curing at 70℃ and 50% humidity for 18h.

Citation Information

Patent Citations

  • Special non-dismantling compound heat-insulating sound board for household floor slabs and construction method thereof

    CN104863295A

  • A formwork-free composite thermal insulation sound insulation board and thermal insulation sound insulation floor construction method

    CN110424625B

  • A method for manufacturing a class a composite thermal and sound insulation board, and a floor structure system

    CN117484672B